2012
DOI: 10.1148/radiol.12110872
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Disease: Diagnosis by Using Diffusion-weighted and Dynamic Contrast-enhanced MR Imaging—Initial Experience

Abstract: DW imaging is a promising tool for differentiating MPD from benign lesions, with high accuracy, and supplementation with DCE MR imaging seems to further improve sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 34 publications
0
71
0
3
Order By: Relevance
“…Ponadto wprowadzenie nowych technik, w tym obrazu zależnego od dyfuzji i dynamicznego wzmocnienia po kontraście, otwiera drogę do jeszcze dokładniejszej oceny budowy struktur antomicznych w przypadku obecności guzów w rzucie osierdzia [122].…”
Section: Rezonans Magnetyczny Sercaunclassified
“…Ponadto wprowadzenie nowych technik, w tym obrazu zależnego od dyfuzji i dynamicznego wzmocnienia po kontraście, otwiera drogę do jeszcze dokładniejszej oceny budowy struktur antomicznych w przypadku obecności guzów w rzucie osierdzia [122].…”
Section: Rezonans Magnetyczny Sercaunclassified
“…They concluded that DWI can differentiate malignant pleural diseases from benign lesions with high accuracy especially with the combination of DCE-MRI. They also concluded that by using a purely ADC-based diagnosis, false-negative diagnoses may occur mostly due to necrotic and inflammatory area within the tumor (12).…”
Section: Resultsmentioning
confidence: 99%
“…It is beginning to be used for the staging and response assessment of lymphomas (7)(8)(9)(10). Because DW-MRI of extracranial lesions has only just begun, there are only a few reports about its usefulness for evaluating pleural disease (11,12) and identifying appropriate areas for biopsies of intrathoracic lesions (13,14). There are no reports about its usefulness for determining optimum biopsy sites of pleural disease.…”
Section: Discussionmentioning
confidence: 99%